2020
DOI: 10.1109/access.2020.2973268
|View full text |Cite
|
Sign up to set email alerts
|

Performance of High-Mobility MIMO Communications With Doppler Diversity

Abstract: Rapid change of the channels in high-speed mobile communications will lead to difficulties in channel estimation and tracking, but can also provide Doppler diversity. In this paper, the performance of multiple-input multiple-output system with pilot-assisted repetitive coding and spatial multiplexing has been studied. With minimum mean square error (MMSE) channel estimation, an equivalent channel model and the corresponding system model are presented. Based on the random matrix theory, the asymptotic expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In QPSK, mobility is even beneficial for FM-OFDM performance as a consequence of the increased Doppler diversity. Doppler diversity [34], [35] is a beneficial consequence of spreading the data over the symbol's duration as per the Eb/N0 (dB) frequency modulation step in Fig. 1.…”
Section: Impact Of the Time Variability Of The Channel With Zero Cuto...mentioning
confidence: 99%
“…In QPSK, mobility is even beneficial for FM-OFDM performance as a consequence of the increased Doppler diversity. Doppler diversity [34], [35] is a beneficial consequence of spreading the data over the symbol's duration as per the Eb/N0 (dB) frequency modulation step in Fig. 1.…”
Section: Impact Of the Time Variability Of The Channel With Zero Cuto...mentioning
confidence: 99%
“…Energy detection can be employed to determine whether the transmitted pilot is a zeropilot or a non-zero pilot by computing the energy of the received pilot signals; the computed energy is then compared with a predefined threshold. The energy of the n -th pilot symbol can be computed as (6):…”
Section: Energy Detection Of Transmitted Pilot Symbolsmentioning
confidence: 99%
“…where 𝐿 ̄ is the number of pilot-signal arrival paths that have been taken into consideration when computing the energy of the observed pilot signal; 𝐿 ̄ also represents the diversity order. To collect all benefits from full diversity offered by multipath fading, all observed signal for the n -th transmitted pilot symbol should be considered in (6), i.e., 𝐿 ̄= 𝐿. After energy calculation, the transmitted pilot symbol can then be determined as (8): where =𝑁 𝑜 is considered as the detection threshold.…”
Section: Energy Detection Of Transmitted Pilot Symbolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Receiver-based diversity combining is a well-known technique which has been deeply studied, maturely developed, and widely applied in different mobile communication systems. For example, a site-based diversity was overviewed in [11] as an effective scheme to mitigate rain attenuation effects on satellites signals at tropical climates, a cluster diversity combining was suggested to accelerate the delivery of indoor autonomous vehicles' emergency alerts with less required rebroadcasts according to [12], a single-input multiple-output (SIMO) structure was presented to combine two downlinks from two receiving nodes by a Maximal Ratio Combiner (MRC) as a part of the study presented in [13] to improve the performance of a nonorthogonal multiple access (NOMA) network, the deep fading consequences inside tunnels were suppressed by utilizing multiple properly spaced antennas in a diversity scheme as confirmed in [14], MRC was deployed to enhance the performance by combining faded signals received by spatially distributed cellular base stations as depicted in [15], and the study conducted in [16] concluded that increasing transmit and receive antennas improved the performance in high-mobility communication systems even when rapidly switching channels.…”
Section: Introductionmentioning
confidence: 99%